Pulmonary metastasectomy for sarcoma-survival and prognostic analysis - Dudek, Wojciech; Schreiner, Waldemar; Mykoliuk, Iurii; Higaze, Mostafa; Sirbu, Horia (Journal of Thoracic Disease, 2019)
Background: Pulmonary metastasectomy (PM) has commonly been performed in patients with controlled metastatic sarcoma. We reviewed our single-institution experience with pulmonary resections for sarcoma to analyse clinical outcome and to identify prognostic factors associated with patient survival.
CRIS-Team WoS Importer:2019-09-20